Tensions for green criminology - Brisman, Avi (Critical criminology, 2017)
This article examines tensions that for the most part exist outside green criminology that could—and should—be brought under the green criminological gaze—issues that are not necessarily the province of green criminology but which have implications for the study of environmental crime and harm. Examples include: the conflicting messages that Western society encounters with respect to "victims" and "survivors"; claims of a lack of future orientation (Hayward 2012) in contrast to assertions of a risk-aversion in late modernity (Giddens 1999); frictions between the "precautionary principle" (Magnus 2008) and "precautionary logic" (Aas 2013); and the peculiarities of the "war on youth" (Grossberg 2001) in an era of "overparenting" (Kamenetz 2015) and "overindulged youth" (Kolbert 2012). The goal of the article is less to promulgate an agenda for green criminology than to heighten awareness of issues and contradictions that may contribute to environmental despoliation and degradation or frustrate efforts to address such harm.